1979
DOI: 10.1111/j.1532-5415.1979.tb01674.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vaginal Flora after Natural or Surgical Menopause

Abstract: A study was made of the cervical and upper vaginal flora in menopausal women, in an attempt to determine whether such women are predisposed to infections when undergoing gynecologic operations. The series comprised 72 women (age range, 44-80 years) classified as follows: a) 35 with a natural menopause, b) 18 with a surgical menopause induced by abdominal panhysterectomy, and c) 19 postmenopausal women after vaginal hysterectomy performed for genital prolapse. The vaginal flora of these menopausal women consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Previous investigators have identified the following organisms on the surface of the genitalia: Staphylococcus epidermidis , viridans streptococci, peptostreptococci, corynebacteria, mycobacteria, various Enterobacteriaceae , Bacteroides spp., Prevotella spp., C. albicans and other yeasts 14 . In addition, the vaginal flora of menopausal women consist predominantly of Gram‐positive bacteria, which are found together with gram‐negative bacteria 15 . In the present study, we found that colonized organisms in GPD were Enterobacteriaceae , CNS, Corynebaterium spp.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous investigators have identified the following organisms on the surface of the genitalia: Staphylococcus epidermidis , viridans streptococci, peptostreptococci, corynebacteria, mycobacteria, various Enterobacteriaceae , Bacteroides spp., Prevotella spp., C. albicans and other yeasts 14 . In addition, the vaginal flora of menopausal women consist predominantly of Gram‐positive bacteria, which are found together with gram‐negative bacteria 15 . In the present study, we found that colonized organisms in GPD were Enterobacteriaceae , CNS, Corynebaterium spp.…”
Section: Discussionsupporting
confidence: 51%
“…14 In addition, the vaginal flora of menopausal women consist predominantly of Gram-positive bacteria, which are found together with gram-negative bacteria. 15 In the present study, we found that colonized organisms in GPD were Enterobacteriaceae , CNS, Corynebaterium spp. or MSSA .…”
Section: Discussionmentioning
confidence: 93%
“…The condition is called senile vaginal atrophy in postmenopausal women and postpartum vaginal atrophy in postpartum women. Both conditions are characterized by dyspareunia, vaginal stinging and tightness, dysuria, vaginal color change, an increase in parabasal cells, a decrease in Lactobacillus species, and an increase in vaginal pH [16][17][18][19][20]. The association of breast-feeding with vaginal atrophy and the resultant absence of Lactobacillus species, along with its potential risks, may be underappreciated.…”
mentioning
confidence: 95%